Pelatihan Pembuatan Desinfektan Berbahan Eko-Enzim di Pondok Pesantren Mambaul Hikmah Kertosono Nganjuk - WAFA, ALIYUL; Huda, Moch. Faizul; fadhli, khotim; Aisyah, Siti Nur (Lembaga Dongan Dosen, 2023)
Islamic boarding schools are institutions that cannot be separated from the socialsystem of Indonesian society. One of the problems of Islamic boarding school is waste management. The aim of this activity is to increase the student’s understanding and ability to process organic waste into marketable materials, namely disinfectant eco-enzyme. Training activities will be carried out in September 2023 at the Mambaul Hikmah Islamic boarding school, Kertosono, Nganjuk, which was attended by 90 studens. Data was obtained thought a questionnaire and analyzed by descriptively. The research was surprising that 95% of participants stated that the trainingactivities were very useful. 93% of psrticipants stated that the activities very helpful, and 89% of participants stated that this activity increased their understanding regarding types of waste, the impact of landfills, and how to made eco-enzyme and disinfectants. The cocluded from the training activity had a positive impact on waste related to the processing of organic waste into marketable material.